Pembelajaran Aswaja Sebagai Implementasi Pendidikan Karakter di SMP Plus Hidayatul Mubtadi’in - Nidhomuddin, M.; Ni’am, M. Syukron; Sukron, M. Imam (Universitas Islam Malang, 2021)
Aswaja learning in an educational environment affiliated with Nahdlatul Ulama, both structurally and culturally, should be teaching. Because, Aswaja is a method of thinking (Minhaj al-Fikr) in seeing all the problems of public life. This point of view will direct Nahdliyin citizens in social and religious action and behavior. One of the important points internalized against the younger generation of Nahdlatul Ulama, is an inclusive perspective in seeing the problems that arise from paradigmatic friction on Islam. Aswaja's paradigm of thought rests on the source of Islamic teachings; al-Qur'an, al-Sunnah, al-Ijma ', and Qiyas. While at the practical level, following the ideas of al-Asy'ari and al-Maturidi in the field of theology, following one of the four imams of the mazhab (Hanafi, Maliki, Shafi'i, and Hanbali) in the field of Fiqh, and following Imam Junaid al-Baghdadi and Imam al-Ghazali in the field of Sufism. Along with the times, ideas and movements to find solutions to educational problems in Indonesia continue to grow. A number of researchers, experts and education practitioners work hand in hand to find the distinctive features of education in Indonesia. Various methods and strategies are used in order to find an educational formulation with distinctive Indonesian characteristics. There are various kinds of character education that are taken from the values of both groups, teachings or certain customs. This new discovery is a form of the responsibility of observers, practitioners and education experts for the face of education in Indonesia. One of them is the idea of ASWAJA Value-Based Character Education